2016
DOI: 10.22436/jnsa.009.05.21
|View full text |Cite
|
Sign up to set email alerts
|

Fixed point theorems for generalized F-contractions in b-metric-like spaces

Abstract: In this paper, we introduce some new F-contractions in b-metric-like spaces and investigate some fixed point theorems for such F-contractions. Presented theorems generalize related results in the literature. An example is also given to support our main result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…Applications of two different types of Volterra type nonlinear integral inclusions and dynamic process are presented. Our results generalized and extended many recent fixed point results of Rasham et al [24,27,28], Wardowski's result [39], Ameer et al [7], and many classical results in the current literature (see [15,21,23,31,32]).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Applications of two different types of Volterra type nonlinear integral inclusions and dynamic process are presented. Our results generalized and extended many recent fixed point results of Rasham et al [24,27,28], Wardowski's result [39], Ameer et al [7], and many classical results in the current literature (see [15,21,23,31,32]).…”
Section: Discussionsupporting
confidence: 88%
“…Hussain et al [20] conceived the new idea of dislocated b-metric spaces and obtained fixed points in common for weak contractive mappings with application on integral inclusions. Afterwards, Chen et al [15] discussed fixed point outcomes for generalized Fcontraction in b-metric like spaces. After this Rasham et al [27] obtained some multivalued fixed point achievements for pairs of F-contractive maps.…”
Section: Introductionmentioning
confidence: 99%
“…We introduced the concept of a pair of graph-dominated mappings and given a fixed-point existence result of a fixed point for graphic contractions. Our results generalized and extended many recent fixed-point results of Rasham et al [16,20], Wordowski's result [28], Ameer et al [6] and many classical results in the current literature (see [4,7,9,13,17,18,23,24]).…”
Section: Discussionsupporting
confidence: 88%
“…Rasham et al [9] proved the multivalued fixed point results for new generalized F-contractive mappings on dislocated metric spaces with application to the system of integral equations. Nazir et al [10] showed common fixed point results for a family of generalized multivalued F-contraction mappings in ordered metric spaces (see also [11][12][13][14][15][16][17][18][19][20][21]). Recently Shoaib et al [7] discussed the results for the family of multivalued mappings satisfying contranction on a sequence in a closed ball in Hausdorff fuzzy metric space.…”
Section: Introductionmentioning
confidence: 99%